Lithium-containing radiator materials for neutron ionization chambers - Petr B. Baskov; Boris S. Salamakha; Yakov V. Glazyuk; Artur A. Namakshinas; Sergey A. Bondarenko; Ilya M. Mushin; Alexander S. Khudin (Nuclear Energy and Technology)
The paper presents the results of material testing for the purpose of obtaining radiator material – acomposite coating with neutron conversion material – for ionization chambers (IC) which contain the 6Li isotope and convert neutron radiation to a flux of high-energy charged particles through the 6Li(n, α)3H nuclear reaction. The proposed method for forming lithium-containing radiator material allows ensuring a high temperature resistance of up to 600 °C and a mechanical strength at the expense of adhesion to the IC electrode material (grade 321 steel). The advantages of a lithium-containing radiator, compared to a boron radiator, are explained by the smaller cross-section of the 6Li-neutron interaction: the smaller efficiency of the "neutron → charged particle" conversion is made up for by a high power density and a prolonged free path of reaction products in the radiator material, which makes it possible to increase the surface density of 6Li atoms, while reducing the extent of "burnup" in neutron fields. The IC electrode radiator material consists of a two-layer composite coating comprising an adhesive silicate layer and a functional neutron-sensitive lithium fluoride layer. Measurements at an alpha spectrometric facility have shown that the coating has a high energy output (~ 2.8·10–3 MeV/neutron), which remains stable after four thermal cycles of up to 600 °C. The coating is resistant to vibration when exposed to frequencies of 35 to 200 Hz. The paper presents the results of testing the IC mockup with a lithium-containing radiator material. When irradiated with a neutron flux of 6·103 cm–2·s–1, the IC mockup sensitivity value was about 10–15A·s·cm2/neutron, which agrees with the calculated value.